(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Congestive heart failure is the inability of the heart to pump enough blood to the body’s tissues. This is a serious problem in the Western world, affecting mostly the adult population. About 6% - 10% of the population aged 65 and over suffer from congestive heart failure. Recent years have witnessed an increase in hospitalization and death rates, despite innovations and innovations in the field of treatment. Damage begins in the heart muscle and continues in an advanced process of continuous change in the shape of the heart (Remodeling), and thus the heart muscle condenses during an attempt to relieve stress. wall, then the ventricle expands and the shape of the heart becomes rounded, this path precedes the appearance of symptoms by several months and even years .